COMPONENT ANALYSIS OF KOREAN WORDS BEOTDA (벗다), PULDA (풀다), TTEDA (떼다) AND KKEUREUDA (끄르다): ANALISIS KOMPONEN MAKNA KATA BAHASA KOREA BEOTDA (벗다), PULDA (풀다), TTEDA (떼다) DAN KKEUREUDA (끄르다) - Nurul Tri Ariyanti; Usmi Usmi (LLDIKTI Wilayah X, 2023)
This research discusses the meaning components of Korean words which related to ‘took off’ meaning. This research aims to analyze the common and diagnostic meaning components within the words of beotda (벗다), pulda (풀다), tteda (떼다), and kkeureuda (끄르다). This research problem formulations focus on the common meaning componentS and diagnostic meaning components from beotda, pulda, tteda, and kkeureuda. This research is elaborated with a qualitative-descriptive method. The procedure in this research is based on the steps of the meaning component research that proposed by Parera (2004). The sources of meaning data and examples that discussed in this study were obtained from the Standards Korean Language Dictionary of the National Institute of Korean Language. The result of this research indicates one common meaning component and 14 diagnostic meaning components found from those four words, those are the meaning component that can show the different meanings of words that are in the same domain. The meaning component classification in this research is based on eight meaning components of object characteristics, six meaning components of the object type, and one meaning component of the probable non-human subject.